СОВЕТ ҲОКИМИЯТИ ДАВРИДА ҚАТАҒОН ОРГАНЛАР - Абдуллаев, А. (SCIENCE and SOCIETY, 2025)
In this article, the revolutionary tribunals, the Supreme Revolutionary Tribunal and the extraordinary investigation commissions established under it, played a special role among the repressive bodies. On November 18, 1918, the revolutionary tribunal of the Central Executive Committee of Turkestan was established, and under them, an investigative commission and a jury of accusers were established.
Keywords: soviet power; repressive bodies; revolutionary tribunal; commission of inquiry; Amudarya administration; charter; judicial chamber